'EU Justice Scoreboard: a new policy tool for "deepening" European integration?'. Issue 1 (2nd January 2019) - Strelkov, Alexander
ABSTRACT: Since its introduction in late 2013, the EU Justice Scoreboard allows the European Commission to obtain information on the performance of national judicial systems. This article argues that despite being a technical policy instrument, the EU Justice Scoreboard has the long-term potential to affect the division of competences between member states and supranational institutions in the domain of rule of law. Drawing on three meta-theories of EU integration, neofunctionalism, new intergovernmentalism and governance, this article investigates which theoretical approach best explains the functioning of this policy instrument. Although it is considered that in the case of the EU Justice Scoreboard, insights from both neofunctionalism and new intergovernmentalism have better explanatory power, this article stresses the need to combine various theoretical accounts for a more comprehensive understanding of EU policy processes.